El estilo cognitivo en el contexto educativo (Papeles, 2009)
This paper presents an overview of the research on the application of cognitive style theory to education. The study consists of three parts: first, the statement of the problem, in which the evolution and the sense given to the concept of “cognitive style” by the psycho-pedagogical research, is presented, second, theory and practice are contrasted with respect to specific educative and pedagogical issues and, finally, a reflection is made on how to face the problem of cognitive differences in educative and  pedagogical settings.
Keywords: Cognitive difference, education, pedagogical practice, learning, field dependency-independency.